Mga2 Transcription Factor Regulates an Oxygen-responsive Lipid Homeostasis Pathway in Fission Yeast - Burr, Risa (J Biol Chem, 2016)
Eukaryotic lipid synthesis is oxygen-dependent with cholesterol synthesis requiring 11 oxygen molecules and fatty acid desaturation requiring 1 oxygen molecule per double bond. Accordingly, organisms evaluate oxygen availability to control lipid homeostasis. The sterol regulatory element-binding protein (SREBP) transcription factors regulate lipid homeostasis. In mammals, SREBP-2 controls cholesterol biosynthesis, whereas SREBP-1 controls triacylglycerol and glycerophospholipid biosynthesis. In the fission yeast Schizosaccharomyces pombe, the SREBP-2 homolog Sre1 regulates sterol homeostasis in response to changing sterol and oxygen levels. However, notably missing is an SREBP-1 analog that regulates triacylglycerol and glycerophospholipid homeostasis in response to low oxygen. Consistent with this, studies have shown that the Sre1 transcription factor regulates only a fraction of all genes up-regulated under low oxygen. To identify new regulators of low oxygen adaptation, we screened the S. pombe nonessential haploid deletion collection and identified 27 gene deletions sensitive to both low oxygen and cobalt chloride, a hypoxia mimetic. One of these genes, mga2, is a putative transcriptional activator. In the absence of mga2, fission yeast exhibited growth defects under both normoxia and low oxygen conditions. Mga2 transcriptional targets were enriched for lipid metabolism genes, and mga2Δ cells showed disrupted triacylglycerol and glycerophospholipid homeostasis, most notably with an increase in fatty acid saturation. Indeed, addition of exogenous oleic acid to mga2Δ cells rescued the observed growth defects. Together, these results establish Mga2 as a transcriptional regulator of triacylglycerol and glycerophospholipid homeostasis in S. pombe, analogous to mammalian SREBP-1.